Analisis Pemahaman Organisasi Keagamaan UKM-KP dan UKM-K FMIPA Mahasiswa dalam menerapkan Nilai-Nilai Pancasila di Lingkungan Kampus Universitas Negeri Medan - Hansel Valent; Parlaungan Gabriel Siahaan; Novridah Reanti Purba; Fatimah Asro; Sovantri Putra Paskah; Raihan Insan Pratama (Penerbit Jurnal Indonesia, 2024)
Pancasila as the ideology and basis of the state plays an important role in shaping the character of students at Medan State University. Through Student Activity Units (UKM), such as UKM-KP and UKM-K FMIPA, Pancasila values are internalized through various social, religious and scientific activities. This research uses qualitative methods with interviews, direct observation and documentation, which are analyzed thematically with source triangulation to ensure data validity. The research results show that activities such as mass, group prayer, social visits, live-ins, democratic deliberations, and social programs play an effective role in instilling the values of Divinity, Humanity, Unity, Democracy, and Social Justice. These findings emphasize the importance of UKM as a forum for developing Pancasila character which is reflected in campus and community life.